Microcapsule-based chemical nickel plating solution and method for preparing coating
By introducing microcapsules into the electroless nickel plating solution, the self-repair function of the coating is achieved, solving the problem of easy and irreparable traditional coatings, extending service life and reducing maintenance costs.
Patent Information
- Application Number
- CN202411796944.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-28
AI Technical Summary
Traditional electroless nickel coatings are susceptible to damage during use and cannot be self-repaired, resulting in corrosion expansion and equipment failure, and lack of self-repair function in high hardness and corrosion-resistant environments.
By introducing microcapsules into the electroless nickel plating solution, the microcapsule shell material adopts polyurea or polyamide, and the core material is the component of the electroless nickel plating solution. The microcapsules release the core material when the coating is damaged, generating new nickel-phosphorus alloy deposits, repairing cracks and preventing the spread of corrosive media.
The self-healing function of the coating is realized, which extends service life, reduces maintenance costs, and maintains good performance in high hardness and corrosion-resistant environments.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical plating, and in particular to a microcapsule-based chemical nickel plating solution and a method for preparing a coating, which can be widely used in the production of surface protective chemical nickel plating layers of industrial equipment requiring long life and corrosion resistance. Background Art
[0002] The chemical nickel plating process is a technology that deposits a nickel layer on the surface of a substrate through a chemical reduction reaction without the need for an external current. Compared with the traditional electroplating process, the chemical nickel plating process has the following advantages: 1. Strong deposition uniformity: It can be deposited evenly on the surface of complex geometric shapes, especially suitable for high-precision parts and inner cavity surface treatment; 2. Excellent corrosion resistance: The chemical nickel plating coating usually contains nickel-phosphorus alloy, and the adjustment of phosphorus content can significantly improve the corrosion resistance of the coating; 3. Good mechanical properties: The chemical nickel plating coating has high hardness and good wear resistance.
[0003] However, with the continuous development of industrial applications, traditional chemical nickel coatings face the following problems and technical bottlenecks: 1. The coating damage cannot be repaired: Chemical nickel coatings are susceptible to mechanical damage or environmental corrosion during use, resulting in microcracks, peeling and other defects. These micro-damages will become the starting point for corrosion expansion and accelerate the failure of the equipment surface. For example: in the marine environment, microcracks will cause salt spray corrosion to expand rapidly; in mechanical equipment, surface wear will cause the coating performance to deteriorate. At present, traditional chemical nickel plating technology cannot achieve self-repair of the coating, and subsequent re-coating or replacement of parts is required, which increases maintenance costs and downtime. 2. Local corrosion problem after coating failure: When the coating is locally damaged, the base metal is exposed to the corrosive environment and is prone to electrochemical corrosion. This corrosion phenomenon is particularly serious in equipment with a long service life (such as marine structures, oil pipelines, and aviation parts), posing a huge challenge to equipment reliability. 3. High-performance coatings that lack self-repairing function: In recent years, self-repairing material technology has gradually become an effective way to solve the problem of coating damage. After being damaged, the self-repairing coating can repair cracks through the chemical or physical action of the material itself, thereby extending the service life of the coating. However, most of the current self-healing technologies are concentrated in the field of polymer coatings, which are suitable for low-load and low-temperature environments, while there is less research on self-healing technologies for high-hardness and corrosion-resistant metal coatings.
[0004] In recent years, self-healing material technology has received widespread attention, among which microcapsule technology is an effective means of self-healing. Microcapsule technology is a technology widely used in the fields of controlled drug release and smart materials. By introducing microcapsules into the material, the storage, release and directional delivery of functional components can be achieved. In the field of self-healing coatings, microcapsule technology is considered to be a very promising technical direction. The microcapsule shell material can protect the repair agent and prevent it from failing during the preparation or storage of the coating; the repair agent in the microcapsule is released in a directional manner when the coating is damaged, automatically filling the cracks and achieving local repair. However, the technology for introducing microcapsules into chemical nickel plating coatings is not yet mature. How to introduce repair agent microcapsules into the chemical nickel plating process while ensuring the mechanical properties and stability of the coating is a technical problem that needs to be solved urgently.
[0005] Based on the above problems and technical trends, it is particularly necessary to develop a nickel plating solution that combines microcapsule technology. By introducing microcapsules, the chemical nickel plating coating is given a self-healing function, which can not only extend the service life of the coating, but also reduce maintenance costs and meet high performance and environmental protection requirements. The introduction of this technology will fill the current technical gap in the field of chemical plating coatings in the direction of self-healing, and has important theoretical significance and practical application value. Summary of the invention
[0006] Aiming at the problems existing in the application of the existing chemical nickel plating coating, the invention provides a microcapsule-based chemical nickel plating solution and a method for preparing the coating.
[0007] The implementation method of the present invention is as follows: a microcapsule-based chemical nickel plating solution comprises the following components (per liter of solution): 20-30 g / L of nickel sulfate hexahydrate, 15-20 g / L of sodium hypophosphite, 10-15 g / L of trisodium citrate, 2-5 g / L of microcapsules, 10-15 g / L of boric acid, 0.5-1.0 g / L of a dispersant, and the balance is deionized water and ammonia water, wherein the amount of ammonia water used can ensure that the pH value of the nickel plating solution is adjusted to 4.5-5.0; the particle size of the microcapsules is 1-5 μm, the shell material of the microcapsules is one of polyurea or polyamide, and the core material of the microcapsules is the component of the chemical nickel plating solution after removing the microcapsules. The present invention introduces microcapsule technology into the chemical nickel plating coating. When the coating surface is mechanically damaged or corroded, the microcapsule shell material is destroyed in the crack propagation area, and the core material in the microcapsule is released to react with the surrounding environment (such as air, chemical components) to generate new nickel-phosphorus alloy deposits. The deposits are deposited in the damaged area of the coating, close the cracks, and prevent the diffusion of corrosive media, thereby repairing the coating. The repaired coating partially restores its corrosion resistance and extends the coating life.
[0008] Preferably, the dispersant is one of sodium dodecylbenzene sulfonate or OP-10.
[0009] Preferably, the preparation method of the microcapsules comprises the following steps: step 1, fully mixing the components of the core material solution to obtain a core material solution; step 2, emulsification: adding the shell material monomer to the core material solution, and forming a stable oil-water emulsion colloid through high-speed shear stirring or ultrasonic emulsification; step 3, polymerization reaction: heating the oil-water emulsion colloid obtained in step 2 to 40-60° C., adding an initiator or catalyst, and conducting an in-situ polymerization reaction for a polymerization time of 2-6 hours to ensure that the shell material forms a complete coating layer on the surface of the core material, and finally generating a microcapsule with a stable structure; step 4, post-processing of the microcapsules: separating the generated microcapsules from the reaction residue by centrifugation, and repeatedly washing with deionized water or ethanol to remove unreacted monomers and impurities; and then drying the microcapsules at 40-60° C. to obtain a microcapsule product with uniform particle size and good shell material integrity.
[0010] The method for preparing a coating by using a chemical nickel plating solution based on microcapsules comprises the following steps: step 1, dissolving nickel sulfate hexahydrate in deionized water to obtain a nickel sulfate solution; step 2, sequentially adding sodium hypophosphite, trisodium citrate and boric acid to the nickel sulfate solution prepared in step 1, stirring evenly to obtain a mixed solution; step 3, adding microcapsules and a dispersant to the mixed solution obtained in step 2, using an ultrasonic disperser to evenly disperse the microcapsules to avoid aggregation, and obtaining a mixed solution containing microcapsules; step 4, further adding ammonia water to the mixed solution containing microcapsules, adjusting the pH of the solution to 4.5-5.0, heating the solution to 80-85°C, and placing the pretreated workpiece into the nickel plating solution for chemical deposition, thereby obtaining a nickel plating coating.
[0011] The present invention aims to solve the problem that traditional chemical nickel plating coatings are easily damaged and cannot be repaired during use. By introducing microcapsule technology, the coating is endowed with self-healing function. The beneficial effects of the present invention include: (1) when the coating surface is damaged, the microcapsules can release the core material as a repair agent to fill the cracks or damage; (2) the coating has high hardness, corrosion resistance and self-healing properties, and is suitable for harsh industrial environments; (3) the present invention provides a stable and environmentally friendly chemical nickel plating process, while ensuring the uniform dispersion and stability of the microcapsules. DETAILED DESCRIPTION
[0012] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Example
[0013] A chemical nickel plating solution based on microcapsules comprises the following components (per liter of solution): 25 g / L nickel sulfate hexahydrate, 18 g / L sodium hypophosphite, 12 g / L trisodium citrate, 3 g / L microcapsules, 12 g / L boric acid, 0.75 g / L dispersant, and the remainder is deionized water and ammonia water, wherein the amount of ammonia water can ensure that the pH value of the nickel plating solution is adjusted to 4.8; the particle size of the microcapsules is between 1 and 5 μm, the shell material of the microcapsules is polyurea, and the core material of the microcapsules is the component of the chemical nickel plating solution after removing the microcapsules; and the dispersant is sodium dodecylbenzene sulfonate.
[0014] The preparation method of the microcapsules comprises the following steps: step 1, preparation of core material solution: fully mixing the components of the core material solution to obtain the core material solution; step 2, emulsification: adding the shell material monomer to the core material solution, and forming a stable oil-water emulsion colloid through high-speed shear stirring; step 3, polymerization reaction: heating the oil-water emulsion colloid obtained in step 2 to 45° C., adding a catalyst of sodium sulfite, and performing an in-situ polymerization reaction for 4 hours to ensure that the shell material forms a complete coating layer on the surface of the core material, and finally generating a microcapsule with a stable structure; step 4, post-processing of the microcapsules: separating the generated microcapsules from the reaction residue by centrifugal separation, and repeatedly washing with deionized water to remove unreacted monomers and impurities; and then drying the microcapsules at 60° C. to obtain a microcapsule product with uniform particle size and good shell material integrity.
[0015] The method for preparing a coating by using a chemical nickel plating solution based on microcapsules comprises the following steps: step 1, dissolving nickel sulfate hexahydrate in deionized water to obtain a nickel sulfate solution; step 2, sequentially adding sodium hypophosphite, trisodium citrate and boric acid to the nickel sulfate solution prepared in step 1, stirring evenly to obtain a mixed solution; step 3, adding microcapsules and a dispersant to the mixed solution obtained in step 2, using an ultrasonic disperser to evenly disperse the microcapsules to avoid aggregation to obtain a mixed solution containing microcapsules; step 4, further adding ammonia water to the mixed solution containing microcapsules, adjusting the pH of the solution to 4.8, heating the solution to 82°C, placing the pretreated workpiece into the nickel plating solution for chemical deposition, and obtaining a coating with a thickness of 20 μm.
[0016] This example uses a carbon steel substrate (Q235 steel) as a nickel-plated workpiece, aiming to verify the self-healing performance and corrosion resistance of the surface coating of carbon steel corrosion-resistant equipment.
[0017] (1) Salt spray corrosion test (self-healing performance test): According to ASTM B117-19 standard, the damaged coating was subjected to a 72-hour salt spray corrosion test using a Q-FOG CCT salt spray test chamber. The test conditions were 35±2°C, and a 5% NaCl solution was sprayed, with the spray volume controlled at 2mL / h. Coating damage method: A 0.2mm wide scratch was made on the coating surface to the substrate (using a standard scratch tool). Performance evaluation: The repair of the scratched area was analyzed by electrochemical testing (open circuit potential recovery test, polarization curve determination) and microstructural observation (SEM and EDS). The results showed that the scratched area self-repaired within 72 hours, and the corrosion resistance was restored to 90% of the initial state.
[0018] (2) Salt spray corrosion resistance after repair: After the coating completed self-repair, it was further subjected to long-term salt spray corrosion test. According to ISO 9227 standard, the salt spray corrosion resistance test was carried out in a 5% NaCl solution, the temperature was controlled at 35±2℃, and the corrosion time was 100h. The test results showed that the repaired coating had a corrosion resistance time of more than 100h in the salt spray environment, and no obvious signs of corrosion were observed. Example
[0019] A chemical nickel plating solution based on microcapsules comprises the following components (per liter of solution): 30 g / L nickel sulfate hexahydrate, 20 g / L sodium hypophosphite, 15 g / L trisodium citrate, 2 g / L microcapsules, 10 g / L boric acid, 1 g / L dispersant, and the remainder is deionized water and ammonia water, wherein the amount of ammonia water used can ensure that the pH value of the nickel plating solution is adjusted to 4.5; the particle size of the microcapsules is 1-5 μm, the shell material of the microcapsules is polyamide, and the core material of the microcapsules is the component of the chemical nickel plating solution after removing the microcapsules; and the dispersant is sodium dodecylbenzene sulfonate.
[0020] The preparation method of the microcapsules comprises the following steps: step 1, preparation of core material solution: fully mixing the components of the core material solution to obtain the core material solution; step 2, emulsification: adding the shell material monomer to the core material solution, and forming a stable oil-water emulsion colloid through ultrasonic emulsification; step 3, polymerization reaction: heating the oil-water emulsion colloid obtained in step 2 to 40° C., adding a catalyst of sodium sulfite, and conducting an in-situ polymerization reaction for 6 hours to ensure that the shell material forms a complete coating layer on the surface of the core material, and finally generating a microcapsule with a stable structure; step 4, post-processing of the microcapsules: separating the generated microcapsules from the reaction residue by centrifugal separation, and repeatedly washing with ethanol to remove unreacted monomers and impurities; and then drying the microcapsules at 40° C. to obtain a microcapsule product with uniform particle size and good shell material integrity.
[0021] The method for preparing a coating by using a chemical nickel plating solution based on microcapsules comprises the following steps: step 1, dissolving nickel sulfate hexahydrate in deionized water to obtain a nickel sulfate solution; step 2, sequentially adding sodium hypophosphite, trisodium citrate and boric acid to the nickel sulfate solution prepared in step 1, stirring evenly to obtain a mixed solution; step 3, adding microcapsules and a dispersant to the mixed solution obtained in step 2, using an ultrasonic disperser to evenly disperse the microcapsules to avoid aggregation, and obtaining a mixed solution containing microcapsules; step 4, further adding ammonia water to the mixed solution containing microcapsules, adjusting the pH of the solution to 4.5, heating the solution to 85°C, placing the pretreated workpiece into the nickel plating solution for chemical deposition, and obtaining a coating with a thickness of 15 um.
[0022] In this embodiment, copper material commonly used in connectors of electronic equipment circuit boards is used as a workpiece, aiming to verify the wear resistance, self-repairing ability and hardness performance of the copper-plated surface of the circuit board connector used in electronic equipment.
[0023] 1. Hardness test: Test standard: According to ASTM E384-17 standard, use micro Vickers hardness tester (Wilson VH1102 model) to test the hardness of coating. Test method: Keep the load of 0.1kgf (980.7mN) for 15 seconds, measure the hardness values of different areas of coating respectively, and take the average value as the result. Test result: The Vickers hardness of this coating is 580HV, showing high mechanical strength, which can effectively improve the wear resistance of precision parts of electronic equipment.
[0024] 2. Wear resistance test: Test standard: According to ISO 19252:2008 standard (tribological test method), the wear resistance test was carried out using a reciprocating friction tester (CETR UMT Tribometer). The test adopted a ball-plane contact mode, the friction head material was a steel ball (diameter 6mm, hardness 60 HRC), the load force was 5N, the friction speed was 100mm / s, the friction distance was 100m, and 1000 reciprocating friction cycles were performed.
[0025] Wear surface observation: The wear morphology of the coating surface was observed by an optical microscope (OLYMPUS BX51M), and the crack area after wear was observed by a scanning electron microscope (JEOL JSM-7610F).
[0026] Self-repairing ability: After friction cycles, the micro-crack area on the coating surface undergoes self-repairing. The distribution change of crack-filled elements is confirmed by energy dispersive spectrometer (EDS), and the surface roughness change of the repaired coating is measured by surface profiler (Keyence VK-X250). The results show that after 1,000 friction cycles, the micro-cracks on the coating surface are effectively filled, the surface repair degree is more than 90%, and the coating maintains good functional integrity. Example
[0027] A chemical nickel plating solution based on microcapsules comprises the following components (per liter of solution): 25 g / L nickel sulfate hexahydrate, 18 g / L sodium hypophosphite, 10 g / L trisodium citrate, 4 g / L microcapsules, 15 g / L boric acid, 0.5 g / L dispersant, and the remainder is deionized water and ammonia water, wherein the amount of ammonia water can ensure that the pH value of the nickel plating solution is adjusted to 4.8; the particle size of the microcapsules is 1-5 μm, the shell material of the microcapsules is polyurea, the core material of the microcapsules is the component of the chemical nickel plating solution after removing the microcapsules; and the dispersant is OP-10.
[0028] The preparation method of the microcapsules comprises the following steps: step 1, preparation of core material solution: fully mixing the components of the core material solution to obtain the core material solution; step 2, emulsification: adding the shell material monomer to the core material solution, and forming a stable oil-water emulsion colloid through ultrasonic emulsification; step 3, polymerization reaction: heating the oil-water emulsion colloid obtained in step 2 to 60° C., adding initiator potassium persulfate, and performing in-situ polymerization reaction for 3 hours to ensure that the shell material forms a complete coating layer on the surface of the core material, and finally generating microcapsules with stable structure; step 4, post-processing of the microcapsules: separating the generated microcapsules from the reaction residue through centrifugal separation, and repeatedly washing with deionized water to remove unreacted monomers and impurities; and then drying the microcapsules at 50° C. to obtain microcapsule products with uniform particle size and good shell material integrity.
[0029] The method for preparing a coating by using a chemical nickel plating solution based on microcapsules comprises the following steps: step 1, dissolving nickel sulfate hexahydrate in deionized water to obtain a nickel sulfate solution; step 2, sequentially adding sodium hypophosphite, trisodium citrate and boric acid to the nickel sulfate solution prepared in step 1, stirring evenly to obtain a mixed solution; step 3, adding microcapsules and a dispersant to the mixed solution obtained in step 2, using an ultrasonic disperser to evenly disperse the microcapsules to avoid aggregation, and obtaining a mixed solution containing microcapsules; step 4, further adding ammonia water to the mixed solution containing microcapsules, adjusting the pH of the solution to 4.8, heating the solution to 80°C, placing the pretreated workpiece into the nickel plating solution for chemical deposition, and obtaining a coating with a thickness of 30 μm.
[0030] This embodiment uses a copper tube as a workpiece, aiming to verify the performance of the coating after nickel plating on a copper tube (copper tube, C11000) used in a variable temperature environment, and aims to verify its self-repairing ability and corrosion resistance in a high temperature environment.
[0031] 1. High temperature crack repair capability: Test standard: The coating was tested according to ASTM G123-00 (high temperature corrosion test method). Test conditions: The specimen was placed in a tubular high temperature furnace, the ambient temperature was maintained at 300°C, and the test period was 100 hours. Temperature cycle: Periodic heating and cooling (from room temperature to 300°C, heating / cooling rate 10°C / min, one cycle completed every 10 hours). The morphological changes and crack propagation of the coating surface under high temperature environment were observed by scanning electron microscopy (JEOL JSM-7610F). After the crack was made by controlled scratch method (scratch width 0.1mm), the crack propagation during high temperature exposure was monitored, and the product distribution during the crack repair process was analyzed by SEM combined with energy dispersive spectrometer (EDS). The controlled scratch experiment showed that in a high temperature environment of 300°C, the coating effectively prevented the crack propagation through a self-healing mechanism, and the surface crack area was gradually filled, with no significant signs of expansion.
[0032] 2. High temperature corrosion resistance test: Test standard: According to ASTM G85-19 standard (acid salt spray corrosion test), simulate the corrosion environment to verify the corrosion resistance of the repaired area. Test conditions: Carry out high temperature corrosion test in the corrosive solution (5% NaCl solution, containing 0.3% H2SO4), and the exposure temperature is maintained at 300 ℃. Take samples every 10 hours to test the corrosion performance of the repaired area. Electrochemical corrosion test: Use an electrochemical workstation (Gamry Reference 600+) to measure the potentiodynamic polarization curve and open circuit potential (OCP) of the repaired area. The results show that after 100 hours, the corrosion resistance of the repaired area has recovered to more than 85% of the original performance. Example
[0033] A chemical nickel plating solution based on microcapsules comprises the following components (per liter of solution): 28 g / L nickel sulfate hexahydrate, 18 g / L sodium hypophosphite, 12 g / L trisodium citrate, 3 g / L microcapsules, 10 g / L boric acid, 0.8 g / L dispersant, and the remainder is deionized water and ammonia water, wherein the amount of ammonia water can ensure that the pH value of the nickel plating solution is adjusted to 4.6; the particle size of the microcapsules is 1-5 μm, the shell material of the microcapsules is polyurea, the core material of the microcapsules is the component of the chemical nickel plating solution after removing the microcapsules; and the dispersant is OP-10.
[0034] The preparation method of the microcapsules comprises the following steps: step 1, preparation of core material solution: fully mixing the components of the core material solution to obtain the core material solution; step 2, emulsification: adding the shell material monomer to the core material solution, and forming a stable oil-water emulsion colloid through ultrasonic emulsification; step 3, polymerization reaction: heating the oil-water emulsion colloid obtained in step 2 to 50° C., adding an initiator potassium persulfate, and performing an in-situ polymerization reaction for 3 hours to ensure that the shell material forms a complete coating layer on the surface of the core material, and finally generating a microcapsule with a stable structure; step 4, post-processing of the microcapsules: separating the generated microcapsules from the reaction residue by centrifugation, and repeatedly washing with deionized water to remove unreacted monomers and impurities; and then drying the microcapsules at 60° C. to obtain a microcapsule product with uniform particle size and good shell material integrity.
[0035] The method for preparing a coating based on the above-mentioned microcapsule-based chemical nickel plating solution comprises the following steps: step 1, dissolving nickel sulfate hexahydrate in deionized water to obtain a nickel sulfate solution; step 2, sequentially adding sodium hypophosphite, trisodium citrate and boric acid to the nickel sulfate solution prepared in step 1, stirring evenly to obtain a mixed solution; step 3, adding microcapsules and a dispersant to the mixed solution obtained in step 2, using an ultrasonic disperser to evenly disperse the microcapsules to avoid aggregation, and obtaining a mixed solution containing microcapsules; step 4, adding ammonia water to the mixed solution containing microcapsules, adjusting the pH of the solution to 4.6, heating the solution to 82°C, placing the pretreated workpiece into the nickel plating solution for chemical deposition, and obtaining a coating with a thickness of 25 um.
[0036] This embodiment uses 4340 steel structure for aviation as a workpiece, aiming to verify its self-repairing ability and corrosion resistance under fatigue load.
[0037] (1) Fatigue load test Test standard: Fatigue performance test is carried out according to ASTM E466-15 standard (axial fatigue test method for metal materials). Fatigue testing machine: servo hydraulic fatigue testing machine (Instron 8801). Loading conditions: stress ratio R = 0.1 (ratio of minimum stress to maximum stress), maximum stress is 80% of the yield strength of the substrate (900MPa), frequency is 10Hz, and 10 5 Cyclic loading. Crack creation: Prefabricated cracks (width 0.05 mm, depth 0.03 mm) were made on the coating surface to simulate crack defects caused by fatigue load.
[0038] Under fatigue load, the crack propagation was observed, and the crack propagation behavior was evaluated using a scanning electron microscope (JEOL JSM-7610F) combined with fractographic analysis technology. Results: The cracks on the coating surface were effectively filled during the self-repair process, and the cracks did not further expand, showing excellent crack inhibition ability, indicating that the coating has excellent fatigue resistance.
[0039] (2) Corrosion resistance test after crack repair Test standard: The corrosion resistance of the crack repair area was evaluated according to ASTM B117-19 (neutral salt spray test). Test conditions: Salt spray solution: 5% NaCl solution, pH 6.5-7.2. Test temperature: 35±2℃, salt spray rate 2mL / h. Test cycle: After the crack repair is completed, a 100h salt spray corrosion test was performed. The salt spray test chamber used was a Q-FOG CCT salt spray test chamber, and the electrochemical workstation was a Gamry Reference 600+.
[0040] Performance evaluation: The corrosion resistance of the repaired area was analyzed by electrochemical testing (open circuit potential measurement, potentiodynamic polarization curve) and weight loss method. Results: The repaired crack area showed a corrosion resistance recovery rate of more than 90% in the 100-hour salt spray corrosion test, showing its excellent protection performance. Example
[0041] A chemical nickel plating solution based on microcapsules comprises the following components (per liter of solution): 20 g / L nickel sulfate hexahydrate, 15 g / L sodium hypophosphite, 14 g / L trisodium citrate, 5 g / L microcapsules, 12 g / L boric acid, 1 g / L dispersant, and the remainder is deionized water and ammonia water, wherein the amount of ammonia water used can ensure that the pH value of the chemical nickel plating solution is adjusted to 5; the particle size of the microcapsules is 1-5 μm, the shell material of the microcapsules is polyurea, the core material of the microcapsules is the component of the chemical nickel plating solution after removing the microcapsules; and the dispersant is sodium dodecylbenzene sulfonate.
[0042] The preparation method of the microcapsules comprises the following steps: step 1, preparation of core material solution: fully mixing the components of the core material solution to obtain the core material solution; step 2, emulsification: adding the shell material monomer to the core material solution, and forming a stable oil-water emulsion colloid through ultrasonic emulsification; step 3, polymerization reaction: heating the oil-water emulsion colloid obtained in step 2 to 60° C., adding initiator potassium persulfate, and performing in-situ polymerization reaction for 2 hours to ensure that the shell material forms a complete coating layer on the surface of the core material, and finally generating a microcapsule with a stable structure; step 4, post-processing of the microcapsules: separating the generated microcapsules from the reaction residue by centrifugation, and repeatedly washing with ethanol to remove unreacted monomers and impurities; and then drying the microcapsules at 45° C. to obtain a microcapsule product with uniform particle size and good shell material integrity.
[0043] The method for preparing a coating by using a chemical nickel plating solution based on microcapsules comprises the following steps: step 1, dissolving nickel sulfate hexahydrate in deionized water to obtain a nickel sulfate solution; step 2, sequentially adding sodium hypophosphite, trisodium citrate and boric acid to the nickel sulfate solution prepared in step 1, stirring evenly to obtain a mixed solution; step 3, adding microcapsules and a dispersant to the mixed solution obtained in step 2, using an ultrasonic disperser to evenly disperse the microcapsules to avoid aggregation, and obtaining a mixed solution containing microcapsules; step 4, further adding ammonia water to the mixed solution containing microcapsules to adjust the pH value of the solution to 5.0, heating the solution to 80°C, placing the pretreated workpiece in the nickel plating solution for chemical deposition, and obtaining a coating with a thickness of 20 um.
[0044] This example uses API 5L X65 steel pipe as a workpiece to verify the self-repairing ability and wear resistance of the nickel coating in a corrosive environment containing hydrogen sulfide and carbon dioxide.
[0045] (1) Corrosion resistance test Test standard: Evaluate the corrosion resistance of the coating according to NACE TM0177-2016 standard (hydrogen sulfide corrosion test method). Test environment: simulate the corrosion environment of oil and gas fields, the corrosion solution is 3.5% NaCl solution, saturated H2S and CO2 mixed gas (ratio 90% CO2:10% H2S). Test temperature: 60℃, test time is 72h. Crack creation: simulate coating damage by scratch test (scratch width 0.05mm, depth 0.05mm) on the coating surface. Test equipment: AutoclaveEngineers high-pressure reactor is used to simulate H2S / CO2 environmental corrosion.
[0046] Performance evaluation: Corrosion rate: The weight loss of the sample before and after corrosion is measured by weighing, and the corrosion rate is calculated (unit: mm / year). Corrosion resistance after repair: The corrosion resistance of the crack repair area is evaluated in combination with the electrochemical test (potentiodynamic polarization curve) in the Gamry Reference 600+ electrochemical work.
[0047] Results: The corrosion resistance time of the cracked area after repair was extended to twice that of the unrepaired sample, indicating that the self-healing mechanism of the coating effectively enhanced the corrosion protection ability.
[0048] (2) Wear resistance test Test standard: According to ASTM G99-17 standard (pin-on-disc wear test), the wear resistance of the coating is evaluated using a pin-on-disc friction tester (CETR UMT Tribometer). Test conditions: Wear mode: pin-on-disc contact mode, the pin is steel (diameter 6mm, hardness 60 HRC), test parameters: load: 5N; sliding speed: 200mm / s; friction distance: 500m; test sample: crack area on the coating surface after repair. The friction coefficient is measured by a wear tester (CETR UMT Tribometer) and compared with the initial friction coefficient of the coating. The wear volume is measured using a 3D surface profiler (Keyence VK-X250) to analyze the wear resistance of the coating before and after repair. The test results are: Corrosion resistance: After the crack area is self-repaired, its corrosion resistance time is significantly extended, reaching more than twice that of the unrepaired area, showing excellent corrosion resistance.
[0049] Wear resistance: The friction coefficient of the repaired coating surface is restored to 90% of the initial value, showing good wear resistance and self-healing ability.
Claims
1. A microcapsule-based chemical nickel plating solution, characterized in that: The invention comprises the following components (per liter of solution): 20-30 g / L nickel sulfate hexahydrate, 15-20 g / L sodium hypophosphite, 10-15 g / L trisodium citrate, 2-5 g / L microcapsules, 10-15 g / L boric acid, 0.5-1.0 g / L dispersant, and the balance is deionized water and ammonia water, wherein the amount of ammonia water can ensure that the pH value of the nickel plating solution is adjusted to 4.5-5.0; the particle size of the microcapsules is 1-5 μm, the shell material of the microcapsules is one of polyurea or polyamide, and the core material of the microcapsules is the component of the chemical nickel plating solution after removing the microcapsules.
2. The microcapsule-based chemical nickel plating solution according to claim 1, characterized in that: The dispersant is one of sodium dodecylbenzene sulfonate or OP-10.
3. The microcapsule-based chemical nickel plating solution according to claim 1, characterized in that: The preparation method of the microcapsules comprises the following steps: Step 1, preparation of core material solution: fully mixing the components of the core material solution to obtain a core material solution; Step 2: Emulsification: adding the shell material monomer to the core material solution, and forming a stable oil-water emulsion colloid through high-speed shear stirring or ultrasonic emulsification; Step 3, polymerization reaction: heat the oil-water emulsion colloid obtained in step 2 to 40-60°C, add an initiator or catalyst, and carry out in-situ polymerization reaction for 2-6 hours to ensure that the shell material forms a complete coating layer on the surface of the core material, and finally generate a microcapsule with a stable structure; Step 4, post-processing of microcapsules: separate the generated microcapsules from the reaction residue by centrifugal separation, and wash them repeatedly with deionized water or ethanol to remove unreacted monomers and impurities; then dry the microcapsules at 40-60° C. to obtain microcapsule products with uniform particle size and good shell material integrity.
4. According to the microcapsule-based chemical nickel plating solution of claim 3, in step 3 of the preparation method of the microcapsules, the catalyst is sodium sulfite.
5. According to the microcapsule-based chemical nickel plating solution of claim 3, in step 3 of the preparation method of the microcapsules, the initiator is potassium persulfate.
6. A method for preparing a coating using a microcapsule-based chemical nickel plating solution according to any one of claims 1 to 5, characterized in that: The steps include: Step 1, dissolving nickel sulfate hexahydrate in deionized water to obtain a nickel sulfate solution; Step 2: sequentially adding sodium hypophosphite, trisodium citrate and boric acid to the nickel sulfate solution prepared in step 1, stirring evenly to obtain a mixed solution; Step 3, adding microcapsules and a dispersant to the mixed solution obtained in step 2, using an ultrasonic disperser to evenly disperse the microcapsules to avoid aggregation, and obtaining a mixed solution containing microcapsules; Step 4: Add ammonia water to the mixed solution containing the microcapsules, adjust the pH value of the solution to 4.5-5.0, heat the solution to 80-85° C., place the pretreated workpiece in the nickel plating solution for chemical deposition, and obtain a nickel plating coating.
Citation Information
Cited By
Improved photoelectric coupler packaging electroplating process
CN120119248A
Connector surface composite coating and preparation process thereof
CN120830139A
Low-stress tinning additive and preparation method and application thereof
CN120945448A